2022
DOI: 10.3390/insects13030293
|View full text |Cite
|
Sign up to set email alerts
|

Different Distribution Patterns of Hoverflies (Diptera: Syrphidae) and Bees (Hymenoptera: Anthophila) Along Altitudinal Gradients in Dolomiti Bellunesi National Park (Italy)

Abstract: Hoverflies (Diptera: Syrphidae) and bees (Hymenoptera: Anthophila) are two key taxa for plant pollination. In the present research, the altitudinal distribution of these taxa was studied along two gradients (elevation range: 780–2130 m) in the Dolomiti Bellunesi National Park (Northeastern Italy). Pan traps were used as a sampling device to collect both hoverflies and bees. Other than altitude, the effect of landscape complexity and plant diversity were considered as potential predictors of hoverfly and bee ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…At high altitudes, hoverflies replace small solitary bees due to their better adaptation to harsh alpine conditions (McCabe & Cobb, 2021; McCabe, Colella, et al, 2019; Sommaggio et al, 2022). A recent review, indicated temperature as the main driver of this bee‐to‐fly transition, showing that below 4.9°C, the pollinator communities were fly dominated, while above 5.7°C were bee dominated (McCabe & Cobb, 2021); yet, other factors like the tree canopy cover or precipitation may also play a role (McCabe, Cobb, et al, 2019; McCabe, Colella, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At high altitudes, hoverflies replace small solitary bees due to their better adaptation to harsh alpine conditions (McCabe & Cobb, 2021; McCabe, Colella, et al, 2019; Sommaggio et al, 2022). A recent review, indicated temperature as the main driver of this bee‐to‐fly transition, showing that below 4.9°C, the pollinator communities were fly dominated, while above 5.7°C were bee dominated (McCabe & Cobb, 2021); yet, other factors like the tree canopy cover or precipitation may also play a role (McCabe, Cobb, et al, 2019; McCabe, Colella, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At high altitudes, hoverflies replace small solitary bees due to their better adaptation to harsh alpine conditions (McCabe & Cobb, 2021;McCabe, Colella, et al, 2019;Sommaggio et al, 2022).…”
Section: Impact Of Altitude On Local (α-) Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…This value in our region is 87%, which is logical since the deep Carpathian Basin is more exposed to Mediterranean effects than the Atlantic Netherlands. According to Sommagio et al [113], in addition to the catastrophic decline in the number of hoverflies, mountainous regions are able to provide shelter for them, but this is not true for bumblebees. They observed that the two taxa showed different distribution patterns: hoverflies had a unimodal distribution (richness and abundance) with a peak at middle altitude (1500 m), while bees had a monotonic decline with increasing altitude.…”
Section: Dipteramentioning
confidence: 99%
“…To ensure comprehensive data collection, we carefully considered several factors when choosing our study sites. Primarily, we focused on capturing a uniform range of elevations within the alpine grassland to capture the full spectrum of syrphid diversity patterns in study sites [37]. This approach allowed us to account for potential variations in syrphid communities driven by different grassland types at the same elevation (~989 m).…”
Section: Study Sitesmentioning
confidence: 99%